Loss of flexion during bronchoscopy: a physical experiment and case study of commercially available systems. (December 2017) - O'Shea, Conor; Khan, Kashif Ali; Tugwell, Josef; Cantillon-Murphy, Pádraig; Kennedy, Marcus P
During routine endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) procedures, especially with biopsy of lymph nodes in or around the left upper lobe, frequent reports have noted the loss of ultrasound image and needle angulation leading to an inability to biopsy nodes visualised by EBUS. The aim of this research was to investigate and compare this loss of angulation with commercially available scopes. Bench-top experiments and a clinical case study demonstrated the varying loss of scope angulation, flexibility and manoeuvrability with different scopes and biopsy instruments leading to procedural implications. Improvements in both the EBUS scope and needle characteristics are required to overcome this limitation which has implications in bronchoscope navigation and the diagnostic yield of EBUS-TBNA.